Chronic myelomonocytic leukemia: A rare hematologic malignancy that needs due consideration - Temesgen Assefa; Yosef Alebel (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
Chronic Myelomonocytic Leukemia (CMML) is a malignant hematopoietic stem cell disorder with clinical and pathological features of both a myeloproliferative neoplasm and myelodysplastic syndrome [1]. According to the 2016 WHO classification of hematologic malignancies it is categorized as MyeloDysplastic /Myeloproliferative Neoplasm [2].